2020
DOI: 10.1371/journal.pcbi.1007935
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynamics for confidence-weighted learning

Abstract: Learning in a changing, uncertain environment is a difficult problem. A popular solution is to predict future observations and then use surprising outcomes to update those predictions. However, humans also have a sense of confidence that characterizes the precision of their predictions. Bayesian models use a confidence-weighting principle to regulate learning: for a given surprise, the update is smaller when the confidence about the prediction was higher. Prior behavioral evidence indicates that human learning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 115 publications
(187 reference statements)
6
34
0
Order By: Relevance
“…Evidence for a sensitivity to confidence of prior knowledge in humans has been reported in a variety of tasks and modalities [96,97,98]. This further speaks to the possibility that CS informs belief updating, as confidence has been suggested to modulate belief updating for other modalities in the literature [99,100] and is explicitly captured in terms of belief precision by other promising Bayesian models [101,102,103]. We suspect that, similarly, confidence concerns the influence of new observations on current beliefs in somatosensation.…”
Section: Discussionmentioning
confidence: 68%
“…Evidence for a sensitivity to confidence of prior knowledge in humans has been reported in a variety of tasks and modalities [96,97,98]. This further speaks to the possibility that CS informs belief updating, as confidence has been suggested to modulate belief updating for other modalities in the literature [99,100] and is explicitly captured in terms of belief precision by other promising Bayesian models [101,102,103]. We suspect that, similarly, confidence concerns the influence of new observations on current beliefs in somatosensation.…”
Section: Discussionmentioning
confidence: 68%
“…Theoreticians have studied different models of surprise-based learning, in the absence of reward (see [Gerstner et al, 2018] for a review). More recently, making use of fMRI [Meyniel and Dehaene, 2017], EEG [Jepma et al, 2016, Nassar et al, 2019 or MEG [Meyniel, 2019] techniques, it has been shown that this surprise signal is controlled by confidence. Confidence has been shown to grade the reward signal and impact the subsequent learning in a categorization task with mice [Lak et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…The idea that confidence plays a role in learning has been proposed [Summerfield and De Lange, 2014, Meyniel and Dehaene, 2017, Meyniel, 2019. Within the framework of drift-diffusion models and taking a Bayesian viewpoint, [Drugowitsch et al, 2019] have shown that the optimal learning rate for categorization tasks should depend on the confidence in one's decision, where confidence is defined as the probability of having answered correctly.…”
mentioning
confidence: 99%
“…Based on previous evidence in other sensory domains, we hypothesised that subjects use an optimal Bayesian strategy to infer the statistics over time (Meyniel, 2020;Meyniel et al, 2016). We fit subjects' ratings to four variations of a Bayesian model, according to two factors: first, sequence inference through stimulus frequency (by assuming the sequence as generated by a Bernoulli process, where subjects track how often they encountered previous stimuli), versus inference through transition probability (by assuming the sequence follows a Markov transition probability between successive stimuli, where the subject tracks such transition of previous stimuli).…”
Section: Model Choicementioning
confidence: 99%